2010
DOI: 10.1007/s10592-010-0155-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the domestication state of ackee (Blighia sapida K.D. Koenig) in Benin based on AFLP and microsatellite markers

Abstract: Ackee (Blighia sapida) is a native multipurpose species important for the livelihoods of the rural populations in Benin. Trees are found in natural forests or are managed by farmers in different traditional agroforestry systems. Genetic variation at amplified fragment length polymorphism (AFLP) markers, four nuclear microsatellites (nSSRs) and one chloroplast microsatellite (cpSSR) were investigated in 279 individuals from six wild and eight cultivated populations from Benin. The AFLP data revealed moderate le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Generally, species with a wide distribution, wind dispersal and outcrossing show high genetic diversity 25 , however, based on EST-SSR markers, Calotropis displays a moderate genetic diversity ( H S = 0.245). This level is comparable to the genetic diversity in Blighia sapida , a woody perennial species widespread in tropics and subtropics which had an average genetic diversity of H S = 0.29 26 . It seems that the genetic diversity of Calotropis plants is lower than that of most outcrossing species 25 .…”
Section: Discussionmentioning
confidence: 58%
“…Generally, species with a wide distribution, wind dispersal and outcrossing show high genetic diversity 25 , however, based on EST-SSR markers, Calotropis displays a moderate genetic diversity ( H S = 0.245). This level is comparable to the genetic diversity in Blighia sapida , a woody perennial species widespread in tropics and subtropics which had an average genetic diversity of H S = 0.29 26 . It seems that the genetic diversity of Calotropis plants is lower than that of most outcrossing species 25 .…”
Section: Discussionmentioning
confidence: 58%
“…In general, a weak impact of humans on genetic structure within the research area was observed as ‘homestead' and ‘wild' stands were only weakly differentiated. Nonsignificant isolation‐by‐distance patterns for ‘homestead' and ‘wild' stands of baobab also contradicted the idea of human intervention as shown for the on‐farm timber tree Vitex fisheri in Kenya (Lengkeek et al, 2006) or Blighia sapida in Benin (Ekué et al, 2011). However, the long life cycle of baobab, the enhanced genetic diversity due to its tetraploidy level (Gulsen et al, 2009; Pock Tsy et al, 2009), its outcrossing mechanisms (Kyndt et al, 2009), as well as the unknown settlement history and mobility of humans in the surveyed area may prevent a more detailed interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…These markers allow for the analysis of the genetic diversity of the species, seed‐ and pollen‐mediated gene flow and inbreeding, and may even help to predict consequences of climatic fluctuations on genetic structures (Larsen et al, 2009). The approach is particularly effective in evaluating genetic bottlenecks associated with anthropogenic interventions (Hollingsworth et al, 2005; Larsen et al, 2009; Ekué et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the genetic setup itself may play a role in phenotypic variation, although to our knowledge no study has so far analyzed this association in sea buckthorn. Fifth, human-induced plant material exchange, overexploitation, and domestication could have negative consequences on population structures leading to genetic bottleneck effects [33][34][35]. For northern Pakistan, the identification and characterization of superior ecotypes and populations with respect to yield, nutritional characteristics, time of ripening, and genetic constitution are important to allow for the collection of berries of higher nutritional quality and other market demanded properties, such as fruit size and color.…”
Section: Introductionmentioning
confidence: 99%